Intra-cranial efficacy of brigatinib in an ALK-positive non-small cell lung cancer patient presenting leptomeningeal carcinomatosis. (July 2019) - Gaye, Elisabeth; Geier, Margaux; Bore, Paul; Guilloïque, Marine; Lucia, Francois; Quéré, Gilles; Gouva, Sylvie; Robinet, Gilles; Descourt, Renaud
Highlights: Leptomeningeal disease (LMD) in lung cancer is associated to poor prognosis. ALK-TKi brigatinib has increased intracranial activity then other ALK TKIs. Data on brigatinib efficacy on LMD is lacking. Case showing prolonged (>14 months) intra-cranial response to brigatinib. Intra-cranial efficiency of brigatinib over crizotinib- and ceretinib- resistance. Abstract: Objectives: Brigatinib is a second-generation ALK inhibitor which demonstrated activity over crizotinib-resistance, especially on brain metastasis by increased blood-brain penetration. However, its activity on lepto-meningeal disease is unknown and scarcely reported. Materials and methods: We hereby report the case of lepto-meningeal disease in crizotinib- and ceretinib- treated patient who was successfully treated by brigatinib. Results: The patient achieved intracranial response to brigatinib more than 14 months. Conclusion: Our case provides additional data on brigatinib's intracranial activity, not only on brain metastasis but also on leptomeningeal disease, after experiencing resistance to both crizotinib and ceretinib, 1 st and 2 nd generation ALK inhibitors.